3D imaging shows nano- and microparticles are internalized by salmon skin and corneal epithelial cells - Thiyagarajan, Dhivya B.; Stette, Marie H. S.; Afzal, Bilal M.; Ahluwalia, Balpreet S.; Agarwal, Krishna; Dalmo, Roy A.; Wolfson, Deanna L. (Frontiers in Marine Science, 2024)
The rising problem of plastic pollution is becoming one of the major environmental issues for the world. In the ocean, plastics undergo degradation into smaller microplastics (MPs) and nanoplastics (NPs). Wild fish and farmed salmon would likely be exposed to these NPs and MPs both through skin and through skin wounds. Keratocyte cells, located in the skin epithelial layer, are scavenger cells which may remove foreign materials and maintain the salmon’s health. They are therefore first in line to handle and to suffer from MP and NP exposure. While the impacts of MPs have been well studied in many different organisms, much less is known about the effects of NP exposure, particularly at the subcellular level. Here, we have used holotomographic and fluorescence microscopy to show that both skin and corneal salmon keratocyte cells fully internalize 500–1000 nm polystyrene particles, as well as inorganic 500 nm silica particles. The fact that corneal epithelial cells also take up particles is novel. Furthermore, some of these particles likely end up in lysosomal compartments within 2 hours of exposure. Here, we show that both conventional and new modalities of microscopy have a role to play to understand how micro- and nano particles affect epithelial cells.